2005
DOI: 10.1176/appi.ajp.162.10.1957
|View full text |Cite
|
Sign up to set email alerts
|

Industry Sponsorship and Financial Conflict of Interest in the Reporting of Clinical Trials in Psychiatry

Abstract: Author conflict of interest appears to be prevalent among psychiatric clinical trials and to be associated with a greater likelihood of reporting a drug to be superior to placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
175
1
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 303 publications
(191 citation statements)
references
References 21 publications
6
175
1
6
Order By: Relevance
“…For example, zscore neurofeedback aims to alter brain activity in participants to match an averaged signal (Bekelman & Gross, 2003;Perlis et al, 2005), the expansive pharmaceutical literature (Antonuccio, Danton, & McClanahan, 2003;Rabipour, Delpero, & Raz, 2011), prevalent brain training programs (Underwood, 2016), and to a lesser, but non-negligible extent, research on psychological therapies (Lieb, Osten-Sacken, Stoffers-Winterling, Reiss, & Barth, 2016). Even in the absence of financial interest, moreover, comparative studies across behavioral treatment, psychotherapy, and pharmacology, tend to skew findings towards the specific choice-oftreatment espoused by the authors (Luborsky et al, 1999;Maj, 2008).…”
Section: Animals Respond To Eeg-nf But Do Not Respond To Placebosmentioning
confidence: 99%
“…For example, zscore neurofeedback aims to alter brain activity in participants to match an averaged signal (Bekelman & Gross, 2003;Perlis et al, 2005), the expansive pharmaceutical literature (Antonuccio, Danton, & McClanahan, 2003;Rabipour, Delpero, & Raz, 2011), prevalent brain training programs (Underwood, 2016), and to a lesser, but non-negligible extent, research on psychological therapies (Lieb, Osten-Sacken, Stoffers-Winterling, Reiss, & Barth, 2016). Even in the absence of financial interest, moreover, comparative studies across behavioral treatment, psychotherapy, and pharmacology, tend to skew findings towards the specific choice-oftreatment espoused by the authors (Luborsky et al, 1999;Maj, 2008).…”
Section: Animals Respond To Eeg-nf But Do Not Respond To Placebosmentioning
confidence: 99%
“…These findings raise doubts about whether average effects can be generalized to populationwide prevention that aims at having long-term impact. Finally, evidence suggests that independent evaluations report, on average, lower effect sizes than studies conducted by the developers or distributors of a treatment (Friedman and Richter 2004;Perlis et al 2005;Petrosino and Soydan 2005). In prevention research, failed attempts to replicate findings from developer-led studies include substance abuse programs (e.g., Hallfors et al 2006;St.…”
mentioning
confidence: 99%
“…However, numerous studies have shown that the results that are found by an RCT depend on who is paying the bill. Researchers who are paid by drugs companies find results that favour drugs companies (Perlis et al 2005, Baker et al 2003. Here we not need to consider the mechanisms via which this occurs, we just need to note that it happens.…”
Section: Demanding High Epistemic Standards Across the Boardmentioning
confidence: 99%